PLZF promotes compensatory lung growth by increasing HPMEC proliferation and angiogenesis - Jing Peng; Liang Ma; Zhonghui Wang; Yaxi Du; Qunfen Tao; Qiongchuan Wang; Li Zhao (PLoS ONE, 2025)
Angiogenic signaling pathway activation has been shown to accelerate compensatory lung growth (CLG) after unilateral pneumonectomy (PNX). Therefore, studying specific genes regulating angiogenic signaling pathways is a novel strategy to promote CLG. EdU, flow cytometry and tube formation experiments were performed to test the metabolism of human pulmonary microvascular endothelial cells (HPMECs). Western blotting was used to analyze the levels of promyelocytic leukemia zinc finger protein (PLZF), kelch-like ECH-associated protein 1 (Keap1), hypoxia-inducible factor-1α (HIF-1α), hemeoxygenase-1 (HO-1), quinone oxidoreductase (NQO1), nuclear factor E2-related factor 2 (Nrf2) and other proteins. The proliferation of pulmonary endothelial cells was assessed by Ki67 double staining. A unilateral PNX mouse model was constructed, and changes in lung volume and weight were assessed. Our bioinformatics results suggested that PLZF showed a clear downward trend after unilateral PNX. PLZF overexpression significantly promoted HPMECs proliferation and angiogenesis and inhibited their apoptosis. Further studies revealed that both Keap1 overexpression and Nrf2 silencing altered the effects of PLZF overexpression on HPMECs and inhibited their apoptosis. Notably, HIF-1α silencing reversed the effect of PLZF overexpression on HPMECs angiogenesis but not on proliferation or apoptosis. Knockdown of Nrf2 not only affected HPMECs proliferation and apoptosis but also affected angiogenesis. An in vivo study confirmed that PLZF overexpression promoted an increase in residual lung volume and lung weight in mice after unilateral PNX and significantly promoted the proliferation of lung endothelial cells. In conclusion, our study revealed that PLZF promotes HPMECs proliferation and angiogenesis and accelerates CLG by inhibiting Keap1 activation of the Nrf2 and HIF-1α/VEGF signaling pathways.